Siderophore mediated mineralization of struvite: A novel greener route of sustainable phosphate management. (15th September 2021) - Nandre, Vinod; Kumbhar, Navanath; Battu, Shateesh; Kale, Yuvraj; Bagade, Aditi; Haram, Santosh; Kodam, Kisan
Highlights: First report on novel route of siderophore mediated struvite formation. Design of new media with low concentration of phosphate ions. Fastest recovery of struvite by siderophore from the medium. Mechanism of struvite formation understood by computational studies. Removal of phosphate from industrial waste by siderophore demonstrated. Abstract: Efficient and sustainable removal of phosphate ions from an aqueous solution is of great challenge. Herein we demonstrated a greener route for phosphate recovery through struvite formation by using bacterial siderophore. This method was efficient for removal of phosphate as low as 1.3 mM with 99% recovery efficiency. The siderophore produced by Pseudomonas taiwanensis R-12-2 act as template for the nucleation of struvite crystals and was found sustainable for recycling the phosphorous efficiently after twenty cycles. The formation of struvite crystals is driven by surrounding pH (9.0) and presence of Mg 2+ and NH4 + ions along with PO4 3− and siderophore which was further validated by computational studies. The morphology of struvite was characterized by scanning electron microscopy, followed by elemental analysis. Furthermore, our results revealed that the siderophore plays an important role in struvite biomineralization. We have successfully demonstrated the phosphate sequestration by using industrial waste samples, as possible application for environmental sustainability and phosphate conservation. For the first time electrochemical super-capacitance performance of the struvite was studied. The specific capacitance value for the struvite was found to be 320 F g −1 at 1.87 A g −1 and retained 92 % capacitance after 250 cycles. The study revealed the potential implications of siderophore for the phosphate recycling and the new mechanism for biomineralization by sequestering into struvite. Graphical abstract: Image, graphical abstract